Improvement of the quality and safety of alcohol solutions through their adsorptive refining by natural minerals - Melnyk, Lyudmila; Mank, Valeriy (My University, 2010)
This article presents the research results for adsorptive purification of alcoholic solutions from harmful impurities and heavy metals with paligorskite and gydromica. The authors have grounded the mechanism of adsorbing impurities by natural adsorbents.
Keywords: adsorption; natural minerals; water-alcohol solutions; адсорбція; водно-спиртові розчини; природні мінерали; адсорбция; водно-спиртовые растворы; природные минералы; кафедра процесів і апаратів харчових виробництв; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів